2016
DOI: 10.1038/mt.2016.114
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Latently HIV-infected Cells from Antiretroviral Therapy-suppressed Subjects by Engineered Immune-mobilizing T-cell Receptors

Abstract: Persistence of human immunodeficiency virus (HIV) in a latent state in long-lived CD4+ T-cells is a major barrier to eradication. Latency-reversing agents that induce direct or immune-mediated cell death upon reactivation of HIV are a possible solution. However, clearance of reactivated cells may require immunotherapeutic agents that are fine-tuned to detect viral antigens when expressed at low levels. We tested the antiviral efficacy of immune-mobilizing monoclonal T-cell receptors against viruses (ImmTAVs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 59 publications
1
51
0
Order By: Relevance
“…The copy number of any single pMHC is unlikely to be large. This is consistent with a study that found that a recombinant TCR was only able to recognize 8‐46 pMHCs after in vitro infection with HIV . In addition, viruses such as HIV and CMV, are known to downregulate pMHC as an escape mechanism (eg, CMV can downregulate expression from 10 000 to less than 100 copies per cell ).…”
Section: The Challengesupporting
confidence: 90%
“…The copy number of any single pMHC is unlikely to be large. This is consistent with a study that found that a recombinant TCR was only able to recognize 8‐46 pMHCs after in vitro infection with HIV . In addition, viruses such as HIV and CMV, are known to downregulate pMHC as an escape mechanism (eg, CMV can downregulate expression from 10 000 to less than 100 copies per cell ).…”
Section: The Challengesupporting
confidence: 90%
“…Finally, current programs and protocols for HIV eradication, including histone deacetylase inhibitor (HDACi) administration and immunotherapy, reportedly need improved immunotherapeutic strategies to clear virus in reactivated cells and to limit new virus integration (43,55,59,72,73). Selection and expansion of NK cells with high NCR and IFN-␥ inducibility may represent a useful tool to efficiently clear HIV-1 when combined within the frame of virus eradication strategies exploiting latency exit induction and immuno-/antiretroviral therapy (72)(73)(74).…”
Section: Discussionmentioning
confidence: 99%
“…Selection and expansion of NK cells with high NCR and IFN-␥ inducibility may represent a useful tool to efficiently clear HIV-1 when combined within the frame of virus eradication strategies exploiting latency exit induction and immuno-/antiretroviral therapy (72)(73)(74).…”
Section: Discussionmentioning
confidence: 99%
“…3 ImmTACs have already entered clinical trials in melanoma patients (ClinicalTrials.gov identifier NCT02570308). The first in vitro use of an anti-HIV-1 ImmTAV is described in the report by Yang et al as a TCR specific for HIV-1 p17 cloned and genetically linked to an scFv that binds to CD3 + CD8 + T cells (CD8).…”
Section: Referencesmentioning
confidence: 99%
“…2 The only HIV-1 vaccine trial showing any efficacy in humans, the ALVAC-prime AIDSVAX-boost RV144 trial, only reduced the infection rate by 31.2%. 3 The protection afforded in this …”
Section: See Page 2021mentioning
confidence: 99%